2018
DOI: 10.21037/atm.2018.03.28
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity and implications for cancer care in the era of molecular and immune therapies

Abstract: Molecular and immune therapies have revolutionized cancer treatment and improved patient outcomes and survival. However, the pricing of these drugs has become an issue as the cost of cancer care continues to rise significantly. Cost sharing policies have increased out-of-pocket expenses for patients, leading to poorer financial well-being, quality of life, psychosocial health, and treatment adherence. In this review, we briefly examine some factors affecting the pricing of these new targeted therapies; the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 83 publications
(76 reference statements)
0
104
0
Order By: Relevance
“…10 A systematic review of work-related issues among young cancer survivors found that those who returned to work struggled with reduced work productivity that ultimately impacted their income. 11 A cancer diagnosis results in high financial burden, [12][13][14][15][16] and there is an increase in the risk of bankruptcy following a cancer diagnosis. 16 For cancer patients who are <50 years old, the risk of bankruptcy following their cancer diagnosis is particularly high.…”
Section: Introduction/purp Os Ementioning
confidence: 99%
“…10 A systematic review of work-related issues among young cancer survivors found that those who returned to work struggled with reduced work productivity that ultimately impacted their income. 11 A cancer diagnosis results in high financial burden, [12][13][14][15][16] and there is an increase in the risk of bankruptcy following a cancer diagnosis. 16 For cancer patients who are <50 years old, the risk of bankruptcy following their cancer diagnosis is particularly high.…”
Section: Introduction/purp Os Ementioning
confidence: 99%
“…However, increased efforts to address FT are widely believed to be difficult without providing money directly . Trans and Zafar noted that interventions addressing FT could include reducing drug costs, altering reimbursement models, assessing the value of therapies, designing value‐based insurance, and implementing other survivor‐ and provider‐level interventions . In our study, we found that cancer survivors had unmet needs for supportive information, including treatment costs, cancer's potential effects on finances, insurance coverage, and supportive agencies or programs.…”
Section: Discussionmentioning
confidence: 68%
“…The high acquisition cost of CAR-T therapy has been subject to intense discussion. 5,6,39 On the one hand, this therapy seems to offer high added value, given its innovative nature, 1,2 and its potential for cure. 2,40 Moreover, it has been designated as an orphan drug, which often tend to have a high price tag.…”
Section: Acquisition Costsmentioning
confidence: 99%
“…7 Also, patients in different countries may encounter restricted access or refused coverage by payers, 4 or suffer financial toxicity in the US. 6,8 Moreover, many have expressed that this therapy with the current high price would become unaffordable in the future, 5,[9][10][11] because of its potential to treat more cancer types. 1,10,12 Unsurprisingly, immediately upon its first marketing authorization, a question was raised about the production cost of this therapy.…”
mentioning
confidence: 99%